Perlindungan hukum data konsumen dalam transaksi digital: tinjauan hukum islam dan hukum positif pada platform shopee - Syafitri, Putri Intan (Maliki Interdisciplinary Journal, 2025)
Rapid advancements in digital technology, particularly ecommerce platforms like Shopee, have transformed consumer behavior by offering convenience, speed, and product variety. However, these benefits bring significant challenges regarding personal data protection. This article aims to assess legal safeguards for consumer data through the lenses of Indonesian positive law and Islamic law, using a normative and case study approach. Under positive law, Law No. 27 of 2022 on Personal Data Protection defines data subject rights, controller obligations, and imposes administrative and criminal sanctions for violations. Shopee, as a data controller, must uphold principles of transparency, purpose limitation, accuracy, data retention limits, and technical and administrative accountability. From an Islamic law perspective, managing consumer data is seen as a trust (amanah), tied to preserving honor (hifz al-ʿirdh) and wealth (hifz almal), while preventing unjust exploitation. Data usage must uphold justice and prohibited misuse. The analysis reveals implementation gaps and limited consumer awareness, highlighting the need for a holistic legal framework. The integration of statutory regulations and Islamic ethical norms is essential to establish a secure, fair, and sustainable digital ecosystem for consumers.